The Online Teaching System as a Sustainable Way of Learning - Deaconu, Ovidiu; Deaconu, Adrian Marius; Chitonu, Gabriela Cristina; Taus, Daniel (MDPI AG, 2022)
The COVID-19 pandemic, in addition to the sometimes-dramatic effects in the health sector, presented a wide range of challenges for the various sectors of the national economies. This article refers to the effects of the pandemic in the university field, especially for the period of 2021 until now. The period corresponds to the end of the pandemic overlapping with the post-pandemic return to normal. Although at the beginning of the pandemic the effects seemed terrible, being widespread and long-lasting, some effects were still useful and motivational for the “real world”. The effects in question are those of compulsory online teaching, so on a large scale, of all subjects from all disciplines. The authors modeled and implemented a database system that includes several types of tests to generate representative samples from the university population. In the content of the article, two such tests are exemplified for a single one-semester discipline: “Computer programming and programming languages II”. The experience of the authors revealed, by comparison, practical ways to teach the theory provided in the states of functions in the real world, using exclusively the online or the mixed environment. Finally, we provide a brief conclusion and ideas for future work.